Biomarkers at different levels of organisation after atrazine formulation (SIPTRAN 500SC®) exposure in Rhinella schineideri (Anura: Bufonidae) Neotropical tadpoles - Pérez-Iglesias, Juan Manuel [UNESP] (2019)
Brazil is an important consumer of herbicides. In sugarcane cultivation—the country's most extensive agricultural crop—atrazine-based formulations are the principal form of weed control. Several studies have investigated adverse effects of atrazine or their formulations on anurans, but not specifically on Brazilian species. Our aim was therefore to investigate the lethal and sublethal effects of an atrazine-based herbicide in Rhinella schneideri tadpoles and, in particular, effects on the pigmentation system as a new endpoint in ecotoxicological studies. Rhinella schneideri tadpoles at the Gosner-30 stage were exposed to the atrazine-based herbicide formulation, SIPTRAN 500 SC®, in acute bioassays at concentrations of 1.5–25 mg/L. The lethal and sublethal effects induced were analysed at different ecotoxicological levels: organismal level (alterations in behaviour, growth, development, and body mass; morphologic abnormalities), histological level (liver histopathology), the pigmentation system (melanomacrophages and dermal-melanophores), and cellular level (erythrocyte micronucleus formation and other nuclear-abnormalities). This herbicide induced sublethal effects at the organismal level with alterations in swimming and growth and morphologic abnormalities. These results demonstrated that, in anuran tadpoles, the atrazine-based agrochemical increased the frequency of micronucleus formation and other nuclear-abnormalities in erythrocytes and caused liver damage. In addition, we demonstrated for the first time effects of an atrazine-based formulation on the pigmentation system of anuran tadpoles, specifically an increase in the number of melanomacrophages and dermal melanophores. This study is the first to use several widely differing endpoints at different ecotoxicological levels in a comprehensive manner for assessment of the effects of environmental stressors in order to determine the health status of Neotropical anuran species. In doing so, this study establishes a foundation for future ecological assessments. Atrazine-based formulation promotes deleterious effects at different ecotoxicological levels in Neotropical anuran involving hepato- and cytotoxicity.